2003
DOI: 10.1103/physrevb.68.035432
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state properties of nanographite systems with zigzag edges

Abstract: A π-electron network in nanographite systems with zigzag edges exhibits strongly localized edge states, which are expected to have peculiar properties. We study effects of electron-electron interactions on ground-state properties of the systems by means of the weak-coupling renormalization group and the density-matrix renormalization-group method. It is shown that the ground state is a spin-singlet Mott insulator with finite charge and spin gaps. We also find that the edge states are robust against the electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
94
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 29 publications
13
94
0
Order By: Relevance
“…1, we first need to obtain all eigenstates. 18 Making use of the translational invariance along the ribbon direction, we take the partial Fourier transform of x to k x . The operators which diagonalize the Hamiltonian are defined by ͑ဧ͒ = ͚ y ‫ء‬ ͑ဧ , y͒c͑k x , y͒, where with ͑L y +1͒␥ = tanh −1 ͓−tanh͑␥͒͑tЈ + t͒ / ͑tЈ − t͔͒ and the dispersion for the edge state is ͑ဧ͒ = ϯ ͱ tЈ 2 + t 2 −2tЈt cosh͑2␥͒.…”
Section: ͑13͒mentioning
confidence: 99%
See 1 more Smart Citation
“…1, we first need to obtain all eigenstates. 18 Making use of the translational invariance along the ribbon direction, we take the partial Fourier transform of x to k x . The operators which diagonalize the Hamiltonian are defined by ͑ဧ͒ = ͚ y ‫ء‬ ͑ဧ , y͒c͑k x , y͒, where with ͑L y +1͒␥ = tanh −1 ͓−tanh͑␥͒͑tЈ + t͒ / ͑tЈ − t͔͒ and the dispersion for the edge state is ͑ဧ͒ = ϯ ͱ tЈ 2 + t 2 −2tЈt cosh͑2␥͒.…”
Section: ͑13͒mentioning
confidence: 99%
“…13,14 For example, graphene nanoribbons with zigzag edges support localized states at the Fermi energy and cause the accumulation of spin and charge polarization near the edges. [15][16][17][18][19][20] Here we aim to better understand the carrier-mediated exchange coupling on bipartite lattice and use a graphene nanoribbon as an example. We calculate the carrier-mediated exchange coupling using the real-time formalism and find that the results do not agree with the theorem in Ref.…”
mentioning
confidence: 99%
“…Louie et al have also showed that the edge-magnetic nature of ZGNRs can induce half-metallicity in the presence of a transverse electric field across the ribbon width, resulting in a spin current 42 . The edge magnetism in zigzag nanoribbons has also been studied using the mean-field Hubbard model by Jung and coworkers 43 , employing the quantum Monte Carlo technique by Golor et al 44 and by renormalization technique by Hikihara et al 45 and experimentally at room temperature by Magda and coworkers 46 . Instead of the presence of ferromagnetically aligned spins at the edges, all the above studies predicted a singlet ground state in ZGNR in the absence of an external field; however, a few density functional studies predicted a ferromagnetic ground state in ZGNR on doping 47 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9,13 As a simple prototypical system to explore the electronic structure of carbon-based nano-materials, nanographite ribbon had been studied by some theoretical and experimental groups for its special electronic structure properties in recent years. [15][16][17][18][19][20][21][22][23] A kind of peculiar edge state localized at the edge carbon atoms of ribbon had been found near the Fermi level ͑E F ͒ when the ribbon has a zigzag edge ͑denoted as the zigzag ribbon͒. [15][16][17] Dangling-bond states exist in the ribbons without H atom termination, with their eigenenergies depending on the edge type ͑zigzag or armchair͒.…”
Section: Introductionmentioning
confidence: 99%